The association of apolipoprotein in the risk of ST-elevation myocardial infarction in patients with documented coronary artery disease - Astuti Giantini; Nur Gifarani Pratiwi; Renan Sukmawan; Joedo Prihartono; Suzanna Immanuel; Merci Monica Pasaribu; Sri Suryo Adiyanti; Yusuf Bahasoan (International Journal of Cardiology. Cardiovascular Risk and Prevention, 2023)
Introduction: Cardiovascular disease (CVD) is the number one cause of death worldwide, in this case, acute coronary syndrome (ACS) or acute myocardial infarction (AMI) that developed from coronary artery disease (CAD). Several risk factors contribute to AMI. Non-modifiable risk factors are age, sex, race, and family history. Modifiable risk factors include dyslipidemia, hypertension, smoking, diabetes mellitus, as well as recent factors that are considered more specific such as homocysteine, lipoprotein a [Lp(a)], high sensitivity C- reactive protein (hs-CRP), and apolipoprotein. This study aimed to determine the role of apolipoprotein as a risk factor for STEMI. Methods: This study combines three epidemiological designs: a descriptive and cross-sectional correlative study with 62 STEMI patients at the National Cardiovascular Center Harapan Kita and a comparative study of 62 STEMI patients and 20 non-ACS CAD patients at the Universitas Indonesia Hospital. Results and conclusion: The descriptive study showed the level of apoB 80.71 ± 28.3, apoA1 104.93 ± 27.8, apoB/apoA1 ratio 0.78 ± 0.22, and Lp(a) 6.85 (1.0–48.1). ApoB moderately correlates with LDLc (p < 0.001; r = 0.571). ApoA1 weakly correlates with HDLc (p = 0.005; r = 0.379). In comparative study, there were significant differences between the STEMI and non-ACS CAD groups on apoA1 (104.93 ± 27.8 vs. 137.48 ± 26.46), apoB/apoA1 ratio (0.78 ± 0.22 vs. 0.59 ± 0.15), and hs-CRP (2.88 [0.4–215] vs. 0.73 [0.15–8.9]). Multivariate analysis showed that the most significant risk factors for STEMI in this study were hypertension for modifiable factors and apoA1 for apolipoprotein. The apoA1 and apoB/apoA1 ratio examination can be suggested for people who have experienced plaque formation and are at risk for myocardial infarction.